Advances in Understanding High-Mass X-ray Binaries with INTEGRALand Future Directions - Kretschmar, Peter; Furst, Felix; Sidoli, Lara; Bozzo, Enrico; Alfonso-Garzon, Julia; Bodaghee, Arash; Chaty, Sylvain; Chernyakova, Masha; Ferrigno, Carlo; Manousakis, Antonios; Negueruela, Ignacio; Postnov, Konstantin; et al. (New Astronomy Reviews, 2019)
High mass X-ray binaries are among the brightest X-ray sources in the Milky Way, as well as in nearby Galaxies. Thanks to their highly variable emissions and complex phenomenology, they have attracted the interest of the high energy astrophysical community since the dawn of X-ray Astronomy. In more recent years, they have challenged our comprehension of physical processes in many more energy bands, ranging from the infrared to very high energies. In this review, we provide a broad but concise summary of the physical processes dominating the emission from high mass X-ray binaries across virtually the whole electromagnetic spectrum. These comprise the interaction of stellar winds with the high gravitational and magnetic fields of compact objects, the behaviour of matter under extreme magnetic and gravity conditions, and the perturbation of the massive star evolutionary processes by presence in a binary system. We highlight the role of the INTEGRAL mission in the discovery of many of the most interesting objects in the high mass X-ray binary class and its contribution in reviving the interest for these sources over the past two decades. We show how the INTEGRAL discoveries have not only contributed to significantly increase the number of high mass X-ray binaries known, thus advancing our understanding of the population as a whole, but also have opened new windows of investigation that stimulated the multi-wavelength approach nowadays common in most astrophysical research fields. We conclude the review by providing an overview of future facilities being planned from the X-ray to the very high energy domain that will hopefully help us in finding an answer to the many questions left open after more than 18 years of INTEGRAL scientific observations.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; gamma rays: observations; INTEGRAL observatory; pulsars: general; stars: neutron; X-rays: binaries

Revealing the broad iron Kα line in Cygnus X-1 through simultaneous XMM-Newton, RXTE, and INTEGRAL observations - Duro, Refiz; Dauser, Thomas; Grinberg, Victoria; Miskovicova, Ivica; Rodriguez, Jerome; Tomsick, John; Hanke, Manfred; Pottschmidt, Katja; Nowak, Michael A.; Kreykenbohm, Sonja Sophie; Bel, Marion Cadolle; Bodaghee, Arash; et al. (Astronomy & Astrophysics, 2016)
We report on the analysis of the broad Fe Kα line feature of Cyg X-1 in the spectra of four simultaneous hard intermediate state observations made with the X-ray Multiple Mirror mission (XMM-Newton), the Rossi X-ray Timing Explorer (RXTE), and the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The high quality of the XMM-Newton data taken in the Modified Timing Mode of the EPIC-pn camera provides a great opportunity to investigate the broadened Fe Kα reflection line at 6.4 keV with a very high signal to noise ratio. The 4-500 keV energy range is used to constrain the underlying continuum and the reflection at higher energies. We first investigate the data by applying a phenomenological model that consists of the sum of an exponentially cutoff power law and relativistically smeared reflection. Additionally, we apply a more physical approach and model the irradiation of the accretion disk directly from the lamp post geometry. All four observations show consistent values for the black hole parameters with a spin of a 0.9, in agreement with recent measurements from reflection and disk continuum fitting. The inclination is found to be i 30°, consistent with the orbital inclination and different from inclination measurements made during the soft state, which show a higher inclination. We speculate that the difference between the inclination measurements is due to changes in the inner region of the accretion disk.
Keywords: black hole physics; gravitation; X-rays: binaries

The EXTraS project: Exploring the X-ray transient and variable sky - De Luca, A.; Salvaterra, R.; Belfiore, A.; Carpano, S.; D'Agostino, D.; Haberl, F.; Israel, G. L.; Law-Green, D.; Lisini, G.; Marelli, M.; Novara, G.; Read, A. M.; et al. (Astronomy & Astrophysics, 2021)
Temporal variability in flux and spectral shape is ubiquitous in the X-ray sky and carries crucial information about the nature and emission physics of the sources. The EPIC instrument on board the XMM-Newton observatory is the most powerful tool for studying variability even in faint sources. Each day, it collects a large amount of information about hundreds of new serendipitous sources, but the resulting huge (and growing) dataset is largely unexplored in the time domain. The project called Exploring the X-ray transient and variable sky (EXTraS) systematically extracted all temporal domain information in the XMM-Newton archive. This included a search and characterisation of variability, both periodic and aperiodic, in hundreds of thousands of sources spanning more than eight orders of magnitude in timescale and six orders of magnitude in flux, and a search for fast transients that were missed by standard image analysis. All results, products, and software tools have been released to the community in a public archive. A science gateway has also been implemented to allow users to run the EXTraS analysis remotely on recent XMM datasets. We give details on the new algorithms that were designed and implemented to perform all steps of EPIC data analysis, including data preparation, source and background modelling, generation of time series and power spectra, and search for and characterisation of different types of variabilities. We describe our results and products and give information about their basic statistical properties and advice on their usage. We also describe available online resources. The EXTraS database of results and its ancillary products is a rich resource for any kind of investigation in almost all fields of astrophysics. Algorithms and lessons learnt from our project are also a very useful reference for any current and future experiment in the time domain.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Astronomical databases: miscellaneous; Catalogs; Methods: data analysis; X-rays: general